Graphite / SiBCN ceramic surface Mo2C coating and preparation method thereof
The Mo2C coating is coated on the surface of graphite/SiBCN ceramics by liquid phase and treated in a high-temperature environment, which solves the problems of coating density and oxidation resistance, and achieves stable antioxidant protection at high temperatures.
Patent Information
- Application Number
- CN202411752703.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The prior art is difficult to apply the Mo2C coating densely and evenly on the surface of graphite/SiBCN ceramics, and prevent the coating from falling off under high temperature environments, affecting the anti-oxidation performance.
By using the liquid phase method, a dense and uniform Mo2C coating was formed by coating a mixed solution of ammonium molybdate, urea and deionized water on the surface of graphite/SiBCN ceramics and heating was carried out in a high-temperature environment containing H2 and CH4 mixed gases.
The Mo2C coating is densely uniformly coated on the surface of graphite/SiBCN ceramics, and prevents the coating from falling off under a high temperature environment of 1800°C, significantly improving the material's oxidation resistance.
Smart Images

Figure CN119569480A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite material preparation, and in particular relates to a graphite / SiBCN ceramic surface Mo2C coating and a preparation method thereof. Background Art
[0002] Graphite / SiBCN ceramics are widely used inorganic non-metallic materials with excellent mechanical properties and high-temperature stability. Their working environment is mostly a high-temperature oxidation environment. Traditional carbon-based composites oxidize at temperatures above 400°C. Carbon-based composites modified by SiBCN ceramics can increase the oxidation resistance temperature to around 1400°C. Even so, when encountering a strong oxidation environment, graphite / SiBCN composites are still susceptible to oxidation and damage. In order to expand the application prospects of graphite / SiBCN ceramics, a large number of scientists have conducted valuable research, such as adjusting the ceramic content of graphite / SiBCN ceramic composites, improving high-temperature oxidation resistance stability, or adding zirconium-based and hafnium and ultra-high temperature ceramic doping methods to improve the high-temperature oxidation resistance of graphite / SiBCN ceramic composites. These methods have played a certain role in improving high-temperature performance, but it is worth noting that changing the ceramic content in graphite / SiBCN ceramic composites in these methods cannot essentially improve the oxidation resistance of SiBCN ceramics, and it is difficult to evenly compound the ultra-high temperature phase into graphite / SiBCN ceramics by doping ultra-high temperature ceramics. There are still a large amount of graphite or SiBCN ceramics exposed to a strong oxidizing environment, which fails to play a decisive role.
[0003] In order to substantially improve the high-temperature oxidation resistance of graphite / SiBCN ceramic composites, the current better solution is to add a Mo2C coating to the surface of the graphite / SiBCN ceramic composite. Mo2C is a two-dimensional carbide with a high-temperature oxidation resistance of nearly 1800°C. Adding a Mo2C coating can substantially solve the high-temperature oxidation resistance of the composite material and can evenly cover the surface of the composite material, playing an excellent protective role. In addition, Mo2C also has extremely high wear resistance and can resist physical damage under daily working conditions. Generally speaking, the coating method mostly uses vapor deposition to deposit carbide anti-oxidation coatings such as SiC on the surface of the composite material, but the two-dimensional carbide Mo2C is difficult to obtain by vapor deposition. In the prior art, the method for preparing Mo2C coatings is the molten salt method. When preparing the coating by this method, due to wettability and uniformity problems, it is difficult to prepare a relatively dense and uniform Mo2C coating, especially on the surface of graphite / SiBCN ceramics. The coating prepared by the molten salt method is very easy to fall off.
[0004] Therefore, how to solve the problem that Mo2C coating is difficult to coat densely and evenly on the surface of graphite / SiBCN ceramics, and that Mo2C is easy to fall off on the surface of graphite / SiBCN ceramics in a high temperature environment of 1800°C, affecting the oxidation resistance of graphite / SiBCN ceramics, is a technical problem that needs to be solved urgently in this field.
[0005] It should be noted that the above information disclosed in this background technology section is only used to understand the background technology of the present application concept, and therefore, the above description is not considered to constitute information of the prior art. Summary of the invention
[0006] The embodiments of the present disclosure at least provide a Mo2C coating on the surface of a graphite / SiBCN ceramic and a preparation method thereof.
[0007] In the first aspect, an embodiment of the present disclosure provides a method for preparing a Mo2C coating on the surface of a graphite / SiBCN ceramic, comprising the following steps: step S1, adding ammonium molybdate and urea to deionized water, heating and stirring evenly, and obtaining a mixed solution of ammonium molybdate, urea and deionized water after they are completely dissolved; step S2, coating the mixed solution of ammonium molybdate, urea and deionized water obtained in S1 on the surface of the graphite / SiBCN ceramic; step S3, placing the graphite / SiBCN ceramic coated with the mixed solution of ammonium molybdate, urea and deionized water obtained in S2 in a device containing a mixed gas of H2 and CH4 for heating treatment, heating to the reaction temperature and then performing heat preservation treatment, and cooling with the furnace to obtain the Mo2C coating on the surface of the graphite / SiBCN ceramic.
[0008] In an optional embodiment, the molar ratio of ammonium molybdate, urea and deionized water in the mixed solution in step S1 is 10:(10-50):(30-80).
[0009] In an optional embodiment, the temperature of the heating and stirring in step S1 is 60-80°C.
[0010] In an optional embodiment, the graphite / SiBCN ceramic in step S2 may be a graphite block, a SiBCN ceramic block, or a graphite / SiBCN ceramic composite material block.
[0011] In an optional embodiment, the gas ratio of H2 and CH4 in the mixed gas in step S3 is 1:(1-3).
[0012] In an optional embodiment, the purity of H2 in the mixed gas in step S3 is 99.8%-99.998%; the purity of CH4 is 99.8%-99.998%.
[0013] In an optional embodiment, the total time for heating to the reaction temperature in step S3 is 10-20 hours; the heating rate is 1°C / min-10°C / min; the reaction temperature is 1000°C-1200°C; and the insulation time is 1.5-4.5 hours.
[0014] In a second aspect, the present disclosure also provides a graphite prepared by the method described above.
[0015] A Mo2C coating is formed on the surface of the graphite / SiBCN ceramic, wherein the thickness of the Mo2C coating on the surface of the graphite / SiBCN ceramic is 0.5 μm to 3 μm.
[0016] The beneficial effect of the present invention is that the preparation method of the Mo2C coating on the surface of graphite / SiBCN ceramics can obtain the Mo2C coating on the surface of graphite / SiBCN ceramics that cannot be obtained by the vapor deposition method by using the liquid phase method. On the one hand, the present invention uses ammonium molybdate and urea as raw materials and deionized water as solvent, and the raw materials are widely available, the process steps are simple and convenient, the overall process cost is very low, and it is easy to prepare; on the other hand, the present invention can densely and evenly coat the Mo2C coating on the surface of graphite / SiBCN, and in a static oxidation environment of 1800°C, the Mo2C coating is not easy to fall off and the oxidation resistance of the graphite / SiBCN ceramics coated with the Mo2C coating can be significantly improved.
[0017] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention are realized and obtained by the structures particularly pointed out in the description, claims and drawings.
[0018] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, preferred embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1 The surface morphology of the Mo2C coating on the surface of the graphite / SiBCN ceramic obtained in the embodiment provided in Example 1 of the present disclosure after heat treatment at 1100°C;
[0021] Figure 2The cross-sectional views (a, c) of the graphite / SiBCN ceramic without Mo2C coating after heat treatment at 1100°C and the cross-sectional views (b, d) of the graphite / SiBCN ceramic surface with Mo2C coating after heat treatment at 1100°C prepared in this embodiment;
[0022] Figure 3 Energy spectrum of the Mo2C coating on the surface of graphite / SiBCN ceramics prepared in Example 1 provided in the embodiments of the present disclosure under heat treatment at 1100°C;
[0023] Figure 4 Figure 1 is a graph showing the effect of graphite / SiBCN ceramics without Mo2C coating after static oxidation at 1800°C (a) and a graph showing the effect of graphite / SiBCN ceramics with Mo2C coating on the surface prepared in this embodiment after static oxidation at 1800°C (b). DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] As used herein, the phrases "in one embodiment," "according to one embodiment," "in some embodiments," and the like generally refer to the fact that the particular feature, structure, or characteristic following the phrase may be included in at least one embodiment of the present disclosure. Therefore, a particular feature, structure, or characteristic may be included in more than one embodiment of the present disclosure, so that these phrases do not necessarily refer to the same embodiment. As used herein, the terms "example," "exemplary," and the like are used to "serve as an example, instance, or illustration." Any implementation, aspect, or design described herein as "example" or "exemplary" is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. On the contrary, the use of the terms "example," "exemplary," and the like is intended to present concepts in a concrete manner.
[0026] Herein, example embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as "at least one of..." modify the entire list of elements when following a list of elements, rather than modifying individual elements in the list. For example, the expression "at least one of a, b, and c" should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.
[0027] The terms used herein are only used to describe specific exemplary configurations and are not intended to be limited. As used herein, the singular articles "one", "an" and "the" may also be intended to include plural forms, unless it is clearly indicated above that this is not the case. The terms "comprise", "include" and "have" are inclusive, and therefore specify the presence of features, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, elements, components and / or combinations thereof. The method steps, processes and operations described herein should not be interpreted as necessarily requiring them to be performed in the specific order discussed or shown, unless specifically identified as an execution order. Additional or alternative steps may be adopted.
[0028] Generally speaking, coating methods mostly use vapor deposition to deposit carbide anti-oxidation coatings such as SiC on the surface of composite materials, but two-dimensional carbide Mo2C is difficult to obtain by vapor deposition. In the prior art, the method for preparing Mo2C coatings is the molten salt method. Due to the problems of wettability and uniformity when preparing the coating by this method, it is difficult to prepare a relatively dense and uniform Mo2C coating, especially on the surface of graphite / SiBCN ceramics. The coating prepared by the molten salt method is very easy to fall off.
[0029] The defects existing in the above solutions are the results obtained by the inventor after practice and careful research. Therefore, the discovery process of the above problems and the solutions proposed by the present disclosure for the above problems below should be the contributions made by the inventor to the present disclosure during the disclosure process.
[0030] The disclosed embodiment provides a method for preparing a Mo2C coating on the surface of a graphite / SiBCN ceramic, comprising the following steps: step S1, adding ammonium molybdate and urea to deionized water, heating and stirring evenly, and obtaining a mixed solution of ammonium molybdate, urea and deionized water after the ammonium molybdate and urea are completely dissolved; step S2, coating the mixed solution of ammonium molybdate, urea and deionized water obtained in S1 on the surface of the graphite / SiBCN ceramic; step S3, placing the graphite / SiBCN ceramic coated with the mixed solution of ammonium molybdate, urea and deionized water obtained in S2 in a device containing a mixed gas of H2 and CH4 for heating treatment, heating to the reaction temperature and then performing heat preservation treatment, and cooling with the furnace to obtain the Mo2C coating on the surface of the graphite / SiBCN ceramic.
[0031] In some embodiments, specifically, the molar ratio of ammonium molybdate, urea and deionized water in the mixed solution in step S1 is 10:(10-50):(30-80).
[0032] In some embodiments, specifically, the temperature of the heating and stirring in step S1 is 60-80°C.
[0033] In some embodiments, specifically, the graphite / SiBCN ceramic in step S2 may be a graphite block, a SiBCN ceramic block, or a graphite / SiBCN ceramic composite material block.
[0034] In some embodiments, specifically, the gas ratio of H2 and CH4 in the mixed gas in step S3 is 1:(1-3).
[0035] In some embodiments, specifically, the purity of H2 in the mixed gas in step S3 is 99.8%-99.998%; the purity of CH4 is 99.8%-99.998%.
[0036] In some embodiments, specifically, the total time for heating to the reaction temperature in step S3 is 10-20 hours; the heating rate is 1°C / min-10°C / min; the reaction temperature is 1000°C-1200°C; and the insulation time is 1.5-4.5 hours.
[0037] The disclosed embodiment also provides a Mo2C coating on the surface of a graphite / SiBCN ceramic prepared by the method described above, wherein the thickness of the Mo2C coating on the surface of the graphite / SiBCN ceramic is 0.5 μm to 3 μm. Some embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. The following embodiments and features in the embodiments may be combined with each other without conflict.
[0038] Example 1
[0039] The preparation method of this embodiment is as follows:
[0040] Weigh 50 g of ammonium molybdate, 20 g of urea and 100 g of deionized water, put them into a water bath and heat them to 60° C., stir them thoroughly to make them completely dissolved, and obtain a mixed solution of ammonium molybdate, urea and deionized water.
[0041] The graphite / SiBCN ceramic is placed in the mixed solution and immersed, so that the mixed solution of ammonium molybdate, urea and deionized water is coated on the surface of the graphite / SiBCN ceramic.
[0042] The graphite / SiBCN ceramic coated with a mixed solution of ammonium molybdate, urea and deionized water was placed in a high-temperature furnace, the furnace body was evacuated into a vacuum state, and then a mixed gas of H2 and CH4 was introduced, and the gas ratio of H2 to CH4 was 1:2; the temperature was raised to 1100℃ and kept for 2h, and the Mo2C coating on the surface of the graphite / SiBCN ceramic was obtained after it was taken out.
[0043] Example 2
[0044] The preparation method of this embodiment is as follows:
[0045] Ammonium molybdate, urea and deionized water are placed in a water bath and heated to 80° C. The molar ratio of ammonium molybdate, urea and deionized water is 10:50:80. Stir them thoroughly to make them completely dissolved to obtain a mixed solution of ammonium molybdate, urea and deionized water.
[0046] The graphite / SiBCN ceramic is placed in the mixed solution and immersed, so that the mixed solution of ammonium molybdate, urea and deionized water is coated on the surface of the graphite / SiBCN ceramic.
[0047] The graphite / SiBCN ceramic coated with a mixed solution of ammonium molybdate, urea and deionized water was placed in a high-temperature furnace, the furnace body was evacuated into a vacuum state, and then a mixed gas of H2 and CH4 was introduced, and the gas ratio of H2 to CH4 was 1:3; the temperature was raised to 1200℃ and kept for 1.5h, and the Mo2C coating on the surface of the graphite / SiBCN ceramic was obtained after it was taken out.
[0048] Example 3
[0049] The preparation method of this embodiment is as follows:
[0050] Ammonium molybdate, urea and deionized water are placed in a water bath and heated to 75° C. The molar ratio of ammonium molybdate, urea and deionized water is 10:10:30. Stir them thoroughly to make them completely dissolved to obtain a mixed solution of ammonium molybdate, urea and deionized water.
[0051] The graphite / SiBCN ceramic is placed in the mixed solution and immersed, so that the mixed solution of ammonium molybdate, urea and deionized water is coated on the surface of the graphite / SiBCN ceramic.
[0052] The graphite / SiBCN ceramic coated with a mixed solution of ammonium molybdate, urea and deionized water was placed in a high-temperature furnace, the furnace body was evacuated into a vacuum state, and then a mixed gas of H2 and CH4 was introduced, and the gas ratio of H2 to CH4 was 1:1; the temperature was raised to 1000℃ and kept for 4.5h, and the Mo2C coating on the surface of the graphite / SiBCN ceramic was obtained after it was taken out.
[0053] See also Figure 1 ,From the surface morphology images, it can be seen that the Mo2C coating has been ,uniformly coated on the graphite / SiBCN surface.
[0054] See also Figure 2 Figure a shows the state of graphite / SiBCN ceramics before coating with Mo2C coating, and Figure b shows the state of graphite / SiBCN ceramics after coating with Mo2C coating. It can be seen that the surface is denser after coating; Figure c shows the state of graphite / SiBCN ceramics before coating with Mo2C coating, and the surface has an irregular undulating morphology; Figure d shows the state morphology of graphite / SiBCN ceramics after coating with Mo2C coating, and the surface is more uniform.
[0055] See also Figure 3 ,From the energy spectrum image, it can be seen that the element Mo is evenly distributed on the surface of graphite / SiBCN ceramics.
[0056] See also Figure 4 Figure a shows graphite / SiBCN ceramics without Mo2C coating, and Figure b shows graphite / SiBCN ceramics coated with Mo2C coating. From the effect diagram of static oxidation at 1800℃, it can be seen that after coating with Mo2C coating, the holes on the surface of graphite / SiBCN ceramics after oxidation are significantly reduced, indicating that Mo2C coating plays a key role in the oxidation process and effectively improves the oxidation resistance of graphite / SiBCN ceramics.
[0057] In summary, the beneficial effect of the present invention is that the preparation method of the Mo2C coating on the surface of graphite / SiBCN ceramics can obtain the Mo2C coating on the surface of graphite / SiBCN ceramics that cannot be obtained by the vapor deposition method by using the liquid phase method. On the one hand, the present invention uses ammonium molybdate and urea as raw materials and deionized water as solvent, and the raw materials are widely available, the process steps are simple and convenient, the overall process cost is very low, and it is easy to prepare; on the other hand, the present invention can coat the Mo2C coating densely and evenly on the surface of graphite / SiBCN, and in a static oxidation environment of 1800°C, the Mo2C coating is not easy to fall off and the oxidation resistance of the graphite / SiBCN ceramics coated with the Mo2C coating can be significantly improved.
[0058] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing Mo2C coating on the surface of graphite / SiBCN ceramics, characterized in that: The steps include: Step S1, adding ammonium molybdate and urea into deionized water, heating and stirring evenly, and obtaining a mixed solution of ammonium molybdate, urea and deionized water after they are completely dissolved; Step S2, coating the mixed solution of ammonium molybdate, urea and deionized water obtained in S1 on the surface of graphite / SiBCN ceramic; Step S3, placing the graphite / SiBCN ceramic coated with a mixed solution of ammonium molybdate, urea and deionized water obtained in S2 in a device containing a mixed gas of H2 and CH4 for heating treatment, heating to the reaction temperature and then heat preservation treatment, and then cooling with the furnace to obtain a Mo2C coating on the surface of the graphite / SiBCN ceramic.
2. The preparation method according to claim 1, characterized in that In step S1 The molar ratio of ammonium molybdate, urea and deionized water in the mixed solution is 10:(10-50):(30-80).
3. The preparation method according to claim 1, characterized in that: In step S1 The temperature of the heating and stirring is 60-80°C.
4. The preparation method according to claim 1, characterized in that: In step S2 The graphite / SiBCN ceramic can be a graphite block, a SiBCN ceramic block, or a graphite / SiBCN ceramic composite block.
5. The preparation method according to claim 1, characterized in that: In step S3 The gas ratio of H2 to CH4 in the mixed gas is 1:(1-3).
6. The preparation method according to claim 1, characterized in that: In step S3 The purity of H2 in the mixed gas is 99.8%-99.998%; the purity of CH4 is 99.8%-99.998%.
7. The preparation method according to claim 1, characterized in that: In step S3 The total time for heating to the reaction temperature is 10-20 hours; the heating rate is 1°C / min-10°C / min; the reaction temperature is 1000°C-1200°C; and the insulation time is 1.5-4.5 hours.
8. A Mo2C coating on a graphite / SiBCN ceramic surface prepared by the method according to any one of claims 1 to 7, characterized in that: The thickness of the Mo2C coating on the surface of the graphite / SiBCN ceramic is 0.5 μm to 3 μm.